Transcriptional regulation of the rice arginine decarboxylase (Adc1) and S-adenosylmethionine decarboxylase (Samdc) genes by methyl jasmonate - Peremarti, Ariadna (Plant physiology and biochemistry : PPB, 2010)
2010 Elsevier Masson SAS. All rights reserved.